IMPLEMENTASI PEMIKIRAN AHMAD KHALAFULLAH PADA KISAH KAN’AN DALAM AL-QUR’AN - Muhammad Romadoni (UIN ANTASARI BANJARMASIN, 2024)
This article examines the application of Ahmad Khalafullah's thoughts to the story of Canaan. The research methodology used is a qualitative approach based on literature studies, with primary data from the book al-Fann al-Qasasi fi al-Qur'an al-Karim by Ahmad Khalafullah, as well as secondary data in the form of literature related to the story of Kan'an. The analysis was carried out by applying five components of Khalafullah's thinking, namely: Text Collection, Historical Arrangement of Texts, Text Interpretation, Chapter Division and Preparation, Authenticity and Taklid. The results of the study show that the story of Canaan is part of the literary-historical model (adabi tarikhiy), which provides a moral message that faith is an individual responsibility and cannot be inherited through family relationships. The prophet Noah showed infinite affection by inviting Can'an to board the ark, but Can'an chose to rely on his choice so that he drowned with the disbelievers of his time.